Heat sink implementation in back-end of line for self-heating reduction in 22 nm FDSOI MOSFETs. (October 2021) - Halder, Arka; Nyssens, Lucas; Rack, Martin; Lederer, Dimitri; Raskin, Jean-Pierre; Kilchytska, Valeriya
Highlights: Self Heating affects advanced CMOS devices degrading their performance. Variation in output conductance due to self-heating allows for its extraction. Heat sink in the back-end of line helps in evacuating heat from the transistor. Using the sink, 15–30% reduction in thermal resistance is observed. Abstract: This work studies the effect of heat sink in the back-end of line (BEOL) on the self-heating (SH) parameters of transistors in a Fully Depleted Silicon-on-Insulator (FDSOI) technology. The RF characterization technique, which involves S-parameter measurements over a wide frequency range, is used to evaluate SH parameters. Two types of sink configurations in the BEOL are considered; one connected to the gate and the other left floating. We experimentally demonstrate that gate-connected heat sink allows for a reduced self-heating in 22 nm FDSOI devices. Around 15% to 30% reduction in thermal resistance is observed for the gate-connected heat sink in comparison to the floating sink.